Fixed Point Theorems Under New Caristi Type Contraction in Bipolar Metric Space with Applications - Srinuvasa Rao, B; N.V.Kishore, G; Ramalingeswara Rao, S (International Journal of Engineering and Technology, 2018)
In this paper, the existence of fixed-point results in a complete bipolar metric spaces under new caristi type contraction is well established. Some attention gaining consequences are attained through our results. Finally, it presented an illustration which present applicability of the obtained results.Â